2008
DOI: 10.1177/0886260508314331
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Relationship Power, Intimate Partner Violence, and Condom Use Among Minority Urban Girls

Abstract: This study examined the association between sexual relationship power, intimate partner violence, and condom use among African American and Hispanic urban girls. In this sample of 56 sexually active girls, 50% did not use condoms consistently and therefore were at higher risk for acquiring HIV or sexually transmitted diseases (STDs). Teens who experienced more intimate partner violence had a significantly higher likelihood of inconsistent condom use and therefore a greater risk for HIV/STDs. Girls' sense of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
140
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(159 citation statements)
references
References 44 publications
15
140
3
1
Order By: Relevance
“…Furthermore, research suggests "bargaining assertively is construed as congruent with female gender roles in some contexts" (Amanatullah & Morris, 2010: 256). Research has explored the role of female sexual assertiveness in sexual and reproductive health and the likelihood of sexual victimization (Teitelman et al, 2008;Testa et al, 2007;Rickert et al, 2002), but the extent to which it serves as a protective factor for adolescent IPV is less explored.…”
Section: Urban Honduras Urban Brazilmentioning
confidence: 99%
“…Furthermore, research suggests "bargaining assertively is construed as congruent with female gender roles in some contexts" (Amanatullah & Morris, 2010: 256). Research has explored the role of female sexual assertiveness in sexual and reproductive health and the likelihood of sexual victimization (Teitelman et al, 2008;Testa et al, 2007;Rickert et al, 2002), but the extent to which it serves as a protective factor for adolescent IPV is less explored.…”
Section: Urban Honduras Urban Brazilmentioning
confidence: 99%
“…At this point, consistent and correct use of the male condom is the most widely accepted method to prevent HIV transmission among sexually active individuals. However, compared to their Caucasian counterparts, WACB do not consistently use condoms [4][5][6][7][8][9][10], as they tend to have difficulty negotiating its use [10][11][12]. The growing number of cases in these populations suggests that current preventive interventions involving condom promotion are insufficient [13].…”
Section: Opinionmentioning
confidence: 99%
“…Psychological, sexual, and physical violence are important risk factors for HIV [8,19,[58][59][60][61], through three main mechanisms [62]: (1) by forced or coercive sexual relations with an infected partner [58]; (2) by limiting the woman's ability to negotiate safe sex [61]; and (3) by establishing a "pattern" of sexual risk-taking in individuals who have been abused in childhood or adolescence [35,39,[63][64][65][66].…”
Section: Men's Control Over Womenmentioning
confidence: 99%
“…It is reported that when the dating relationship control is low, it is more likely to experience dating violence victimization from partners with intimate relationships [15] [16]. Teitelman et al [16] demonstrate that the lower the dating relationships control, the greater the likelihood of dating violence victimization.…”
Section: Introductionmentioning
confidence: 99%